Utilization of a novel 3D radiologic scoring method to define therapeutic response and surgical candidacy - Rahmanuddin, Syed; Von Hoff, Daniel D.; Chaudhry, Ammar; Guidaben, Danielle; Khan, Marjaan; Boswell, William; Cridebring, Derek; Brase, Jordyn; Fong, Yuman; Motarjem, Pejman; Borazanci, Erkut (Frontiers in Imaging, 2023)
Purpose Neoadjuvant therapy and surgical resection can improve the survival rate of patients who receive a diagnosis of pancreatic cancer and shows to be potentially curative. The aim of this study is to define a novel CT perfusion analytical method by observing the treatment response of pancreatic cancer patients in a neoadjuvant-treated population to determine surgical candidacy. Experimental design This prospective study involved 22 adult patients with pancreatic ductal adenocarcinoma (PDAC). Participants received neoadjuvant therapy (paricalcitol, paclitaxel protein-bound, cisplatin, and gemcitabine) for up to 6 months. The study examined differences in density between the arterial and venous phases of CT scans using a mathematical analysis called the Marley equation. The data was used to assess treatment responses and determined whether a patient can become a surgical candidate. The consideration for surgical candidacy was defined by Dr. Rahmanuddin, termed the “R” score and graphically depicted as the “R” Clock. The R score determined the number of tumor-linked blood vessels. Any vessel associated with tumor involvement received a score of 1. Patients who received a score of 5 or less were eligible for surgery. 3D Tumor volumetric analyses were performed using GE AW 3D software to assess the treatment response associated with tumor perfusion. Results Visual differences in vascular involvement between baseline and final imaging were associated with a higher likelihood of proceeding to surgery. After administration of the neoadjuvant therapy, 81% of patients (18 of 22) received an R score of 5 or less, deeming all of them eligible for surgery. A total of 59% of patients (13 of 22) proceeded with the surgery. Changes in arterial and venous perfusion reflected tumor aggressiveness as defined by the Marley equation. Conclusion CT vessel perfusion using the R score and Marley Equation might be helpful in defining the surgical candidacy of PDAC patients when used in conjunction with 3D tumor volumetric quantification. The parameters defined by the R score determined higher perfusion scores as having greater vascular growth, and patients with tumor involvement of more than six vessels were deemed surgically unresectable. The Marley equation demonstrated tumor aggression via changes in arterial and venous perfusion. Additional studies are needed to further validate these methodologies and assess their clinical utility.